25-hydroxyvitamin D serum levels in patients with high risk resected melanoma treated in an adjuvant bevacizumab trial. Issue 7 (2nd October 2018) - Lipplaa, Astrid; Fernandes, Ricardo; Marshall, Andrea; Lorigan, Paul; Dunn, Janet; Myers, Kevin; Barker, Emily; Newton-Bishop, Julia; Middleton, Mark; Corrie, Pippa
Abstract Background Studies evaluating a relationship of vitamin D in patients with primary melanoma have consistently identified an inverse correlation with Breslow thickness, but an inconsistent impact on survival. Vitamin D in later stages of melanoma has been less studied. Methods Vitamin D was measured in serum from 341 patients with resected stage IIB–IIIC melanoma recruited to the AVAST-M adjuvant melanoma randomised trial, collected prior to randomisation, then at 3 and 12 months. Vitamin D levels were compared with patient demographics, known melanoma prognostic factors, disease-free interval (DFI) and overall survival (OS). Results A total of 73% patients had stage III melanoma, 32% were enroled (and therefore tested) >1 year after primary melanoma diagnosis. Median pre-randomisation vitamin D level was 56.5 (range 12.6–189.0 nmol/L). Vitamin D levels did not significantly vary over 12 months (p  = 0.24). Individual pre-randomisation vitamin D levels did not differ significantly for Breslow thickness, tumour ulceration, or disease stage. Neither did pre-randomisation vitamin D predict for DFI (HR = 0.98 per 10 nmol/L increase; 95% confidence interval (CI) 0.93–1.04, p  = 0.59) or OS (HR = 0.96 per 10 nmol/L increase, 95% CI 0.90–1.03, p  = 0.31). For stage II patients, DFI improved with higher pre-randomisation vitamin D levels for those on bevacizumab (HR = 0.74 per 10 nmol nmol/L increase; 95% CI 0.56–0.97), but not for the observation arm (HR = 1.07 per 10 nmol/L increase; 95% CI 0.85–1.34). Conclusions In this stage II/III melanoma cohort, vitamin D did not correlate with known prognostic markers, nor predict for DFI or OS, but there was some evidence of benefit for patients with stage II disease treated with bevacizumab.